A Locomotion Recognition System Using Depth Images - Tingfang Yan; Yuxiang Sun; Tingting Liu; Chi-Hong Cheung; Max Qing-Hu Meng (2018 IEEE International Conference on Robotics and Automation (ICRA), 2018)
Powered lower-limb orthoses and prostheses are attracting an increasing amount of attention in assisting daily living activities. To safely and naturally collaborate with human users, the key technology relies on an intelligent controller to accurately decode users' movement intention. In this work, we proposed an innovative locomotion recognition system based on depth images. Composed of a feature extraction subsystem and a finite-state-machine based recognition subsystem, the proposed approach is capable of capturing both the limb movements and the terrains right in front of the user. This makes it possible to anticipate the detection of locomotion modes, especially at transition states, thus enabling the associated wearable robot to deliver a smooth and seamless assistance. Validation experiments were implemented with nine subjects to trace a track that comprised of standing, walking, stair ascending, and stair descending, for three rounds each. The results showed that in steady state, the proposed system could recognize all four locomotion tasks with approximate 100% of accuracy. Out of 216 mode transitions, 82.4% of the intended locomotion tasks can be detected before the transition happened. Thanks to its high accuracy and promising prediction performance, the proposed locomotion recognition system is expected to significantly improve the safety as well as the effectiveness of a lower-limb assistive device.